Increased resilience and a regime shift reversal through repeat mass coral bleaching - Nicholas A. J. Graham; Shaun K. Wilson; Cassandra E. Benkwitt; Rodney Bonne; Rodney Govinden; James P. W. Robinson (Ecology Letters, 2024)
Ecosystems are substantially changing in response to ongoing climate change. For example, coral reefs have declined in coral dominance, with some reefs undergoing regime shifts to non‐coral states. However, reef responses may vary through multiple heat stress events, with the rarity of long‐term ecological datasets rendering such understanding uncertain. Assessing coral reefs across the inner Seychelles islands using a 28‐year dataset, we document faster coral recovery from the 2016 than the 1998 marine heatwave event. Further, compositions of benthic and fish communities were more resistant to change following the more recent heat stress, having stabilized in a persistent altered state, with greater herbivory, following the 1998 climate disturbance. Counter to predictions, a macroalgal‐dominated reef that had regime‐shifted following the 1998 disturbance is transitioning to a coral‐dominated state following the 2016 heat stress. Collectively, these patterns indicate that reef systems may be more resilient to repeat heatwave events than anticipated.